Commentary: Typology, Purpose and Value - Saikia, Devalina (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
“Every commentary engages to a lesser or greater extent in the “’bottom-up” activity of explaining individual expressions in the text, thereby aiming to clarify the syntax of the text and to supply paraphrases of its lexical items, phrases and sentences.” (Ganeri, Jonardon, Sanskrit Philosophical Commentary). In India, there is a continuous and cumulative tradition of commentary literature in each branch of knowledge. “Commentary‟ is a generic term which is used for different types of text interpretation methods, such as: vṛtti (e.g. Kāśikāvṛitti of Vāmana-Jayāditya), vārttika (e.g. Ślokavārttika of Kumārilabhaṭṭa), bhāṣya (Nyāṣyabhāya of Vātsyāyana), etc. Furthermore, a complete list of the typology of commentary has been given by Rājaśekhara in his Kāvyamīmāṃsā as: vṛtti, paddhati, bhāṣya, samīkṣā, ṭikā, pañjikā, kārikā and vārttika. Commentary plays a vital role in understanding a text. It is needed to understand the śāstras. Commentary “serve the purpose of bringing about specific ideas….true meaning is ascertained through explanatory commentaries.” (Kumārilabhaṭṭa, Tantravārttika). K.A. Subramania Iyer remarks that “in understanding the meaning of a stanza, a knowledge of the context is essential and it is not always easy to understand it from the stanza itself, it is no wonder that many authors wrote commentaries on their kārikās. (Iyer, K.A. Subramania, Bhartṛhari: A Study of the Vākyapadīya in the Light of Ancient Commentaries,1969, p. 51). Commentary helps its target readers get into the text intensely and conveys the textual meaning to the reader as a mediator. Thus, the purpose and value of a commentary are worth mentioning here. To sum up, the present paper aspires to study the typology, purpose and value of commentary tradition in Indian intellectual tradition.